Robert Jervis, The Meaning of the Nuclear Revolution: Statecraft and the Prospect of Armageddon - Syed Ali Zia Jaffery (CISS Insight Journal, 2020)
Scholars delving into the effects of nuclear weapons, have looked at how vulnerabilities and fears have affected the behaviors of nuclear states. It is argued that when these two factors are mutual, countries will most likely not go down a deadly, dangerous route that leads to colossal carnage. If they, somehow, decide to tread that path, there would be no victors. These two phenomena mutual second-strike capabilities and the shrinking space for and possibility of military victory are weaved together dexterously by one of the most eminent nuclear strategists, Robert Jervis, in one of his acclaimed books titled, “The Meaning of the Nuclear Revolution: Statecraft and the Prospect of Armageddon”. 30 years down the line, the book continues to be critiqued, reviewed and referred to by anyone even remotely interested in concept of deterrence and strategy. That said, the book is not limited to discussing the nuances of nuclear strategy or how deterrence should be viewed vis-à-vis defense, but also delves into how the role of force changes as an instrument of foreign policy. One would be remiss, if the complementarity between this book and another one of Jervis’ classics, ”The Illogic of American Nuclear Strategy” is not accentuated. Both masterpieces are premised on the argument that nuclear weapons have fundamentally changed the nature of warfare and statecraft.